Perception of Dental House Officers Regarding the Management of Medical Emergencies in CMH Lahore Medical College & IOD - Memoona Javed, Saria Khalid, Sarah Ali, Ayesha Asim, Arham Nawaz Chohan, Muhammad Afzal, Junaid Sarfraz Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The main purpose of this study is to assess the knowledge, attitude, experience, and perception about the management of medical emergencies in dental clinics amongst house officers at CMH LMC & IOD. Study Duration: This questionnaire-based descriptive cross-sectional study was conducted between May 2022 and June 2022 at CMH Lahore Medical College and Institute of Dentistry. Material & Methods: A previously tested questionnaire comprised of three parts was used for data collection. A total of 62 house officers were present. All of them responded to the questionnaire. The questionnaire consists of three sections; Section A: Contains the questions related to the understanding of the dental house officers in managing medical emergencies. Section B: Includes the evaluation of experiences and skills they have in managing medical emergencies if it occurs in dental clinics. Section C: Includes their perceptions related to the betterment of emergency management was evaluated. Data was analyzed using IBM SPSS Version 24. Data was analyzed using IBM SPSS Version 24. Results: Concerning Basic life support training, 64.5% had been given training during house job only. At least 67.7% of House officers came across 1-5 medical emergencies during their house job. Syncope was one of the most common (62.9%). Hypoglycemia was the second most common (35.5%) and asthma was reportedly the third most common medical emergency (1.6%). When facing a medical emergency, 90.3% report that they seek help. 96.8% reported that they can take a patient’s blood pressure, 72.4% can take a patient’s pulse, 27.4% can measure blood sugar level, only 38.7% can maintain an IV line, 41.9% can perform the Heimlich maneuver, 53.2% can carry out ventilation through a bag or mask and 35.5% are capable of performing CPR. Only 3.2% of house officers believe that their undergraduate training is sufficient to prepare them to manage medical emergencies. Though, 71.0 % think that house officers should undertake medical emergency training before starting their house job. Practical implication:There is scarcity of literature on how prepared dental house surgeons are to deal with medical emergencies so this study give future directions to dental house surgeons. Conclusion: It was concluded that practical training is lacking among dental house officers in managing medical emergencies and that there is a need to not only include medical emergency training at the undergraduate level but also allot a rotation to medical emergencies at the start of the house job. Keywords: Dental house officers, medical emergencies, management, training